2021
DOI: 10.1038/s41598-021-93213-9
|View full text |Cite
|
Sign up to set email alerts
|

A susceptibility locus in the IL12B but not LILRA3 region is associated with vascular damage in Takayasu arteritis

Abstract: HLA-B*52 is an established genetic factor in Takayasu arteritis (TAK). Recently, single nucleotide polymorphisms (SNPs) in IL12B (rs6871626) and LILRA3 (rs103294) were newly identified as non-HLA susceptibility loci in TAK. Here, we examined how these SNPs contribute to clinical characteristics and vascular damage in TAK. We retrospectively reviewed the medical records of 99 TAK patients enrolled in our previous genome-wide association study, and whose genotypes for IL12B rs6871626, LILRA3 rs103294, and HLA-B*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Furthermore, GWAS has identified IL-12B as a susceptibility gene for TAK ( 12 , 107 ), and the IL-12B risk allele is associated with vascular damage in TAK ( 108 ). IL-12 relies on the JAK-STAT pathway for intracellular signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GWAS has identified IL-12B as a susceptibility gene for TAK ( 12 , 107 ), and the IL-12B risk allele is associated with vascular damage in TAK ( 108 ). IL-12 relies on the JAK-STAT pathway for intracellular signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a genome-wide association study identified IL-12B as a susceptibility gene for TAK ( 36 , 37 ). Serum IL-12 levels are elevated in TAK patients ( 38 ), and the risk allele of IL-12B is closely associated with vascular damage in TAK ( 39 ). IL-12 uses the JAK-STAT pathway, and JAK2 and TYK2 are located in the downstream signaling pathway ( 40 ).…”
Section: Jak Inhibitors For Vasculitismentioning
confidence: 99%
“…Contrast enhanced ultrasound (CEUS), a technique that is used to assess intraplane neovascularization of carotid artery atherosclerotic plaque, has recently found a place in assessment of disease activity in TA (76). In a retrospective study done on Chinese TA patients, CEUS vascularization score was found to positively correlate with vascular 18 F-FDG PET/CT (Fluorine-18 -Fluoro-Deoxy-glucose [ 18 F-FDG] Positron Emission Tomography [PET]/Computed Tomography [CT]) uptake (77). Ma et al demonstrated the usefulness of this technique for monitoring response to treatment with reduction in parameters like thickness and vascularization, that were specific to TA (78).…”
Section: Contrast Enhanced Ultrasoundmentioning
confidence: 99%
“…Offering a combination of both anatomical and metabolic imaging, PET-CT has a unique place in diagnosis, especially for patients with atypical presentations, those with normal inflammatory markers (81) and presumably for monitoring of treatment response and predicting relapses (82). In a metaanalysis, from 10 studies, pooled Sensitivity and Specificity of 18 F-FDG-PET for TA activity was 81 and 74%, respectively (83). It is however influenced by treatment with glucocorticoids, and should not be performed more than 3 days after starting glucocorticoids as it was found to reduce uptake in vessel wall (84).…”
Section: Pet-ctmentioning
confidence: 99%
See 1 more Smart Citation